(untitled) (Research, Society and Development, 2022)
Patient safety has been a topic of discussion in health institutions, especially in Pediatric Intensive Care Units, since errors and their consequences are more serious in intensive care patients. Pharmaceutical intervention is part of pharmacotherapeutic monitoring and requires record, carried out jointly between health professionals and the patient, with the purpose of preventing and solving negative clinical results. Thus, the aim of this work is to evaluate the profile of pharmaceutical interventions performed by clinical pharmacy in pediatric patients admitted to the Pediatric Intensive Care Unit (PICU) of the Materno Infantil University Hospital in São Luís - MA. This is a quantitative, retrospective and cross-sectional study, based on a survey of data provided by the clinical pharmacy carried out through the analysis of the medical records of pediatric patients, from which information on pharmaceutical interventions recorded was taken in the database from January 2017 to December 2018. A total of 1003 interventions were obtained through participation in multidisciplinary visits at the PICU by pharmacists from the clinical pharmacy team. Of these 1003 pharmaceutical interventions, 98% (n= 983) were accepted and found to have a higher prevalence, in 2017, dose/dosage adjustment 51% and the most suitable therapeutic alternative available 25%. Additionally, in the 2018 period, there was a 37% drop in dose/dosing adjustment. It is concluded that pharmaceutical interventions contributed to the reduction of errors related to the pharmacotherapy of these children and also to the improvement of their clinical condition, a cutback in treatment costs and in the hospitalization period.